1997
DOI: 10.1111/j.1469-7610.1997.tb01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Dieting: Healthy Weight Control or Borderline Eating Disorder?

Abstract: Dieting in adolescent girls is ubiquitous but its health significance is uncertain. On the one hand it might be seen as promoting healthy weight control and on the other it might be considered as a risk factor for eating disorders. Dieting levels were systematically assessed in a representative group of 2525 Australian teenagers and classified using item response theory. In this group, 38% of girls and 12% of boys were categorised as intermediate dieters; 7% of girls and 1% of boys fell into a group of extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 36 publications
1
41
1
4
Order By: Relevance
“…In 2013-2014, an estimated 31.6% of Australian adolescents experienced DE. Notwithstanding differences in how DE is defined, this estimate is similar to those from previous Australian studies (Grigg et al, 1996;Mond et al, 2017;Patton et al, 1997;Paxton et al, 1991) and within the range of estimates from the United States (Neumark-Sztainer et al, 2011). DE was more prevalent in girls than boys, but it was not uncommon in boys, consistent with previous Australian research (Mond et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…In 2013-2014, an estimated 31.6% of Australian adolescents experienced DE. Notwithstanding differences in how DE is defined, this estimate is similar to those from previous Australian studies (Grigg et al, 1996;Mond et al, 2017;Patton et al, 1997;Paxton et al, 1991) and within the range of estimates from the United States (Neumark-Sztainer et al, 2011). DE was more prevalent in girls than boys, but it was not uncommon in boys, consistent with previous Australian research (Mond et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…General population studies of eating attitudes focusing on dieting features that are similar to those Using sex differences in psychopathology to study causal mechanisms seen in anorexia nervosa, but which are much milder, have shown a similar marked female preponderance (e.g., Patton et al, 1997). It may be concluded that, however defined, and whatever severity threshold is used, eating disorders arising in adolescence are very much commoner in females than males.…”
Section: Disorders With a Female Preponderancementioning
confidence: 99%
“…For example, in a community-based weight-gain prevention programme, 22% of women and 17% of men reported the use of at least one unhealthy weight reduction behaviour over the past year (7). Furthermore, it has been well established that body mass index (BMI) is strongly associated with dieting frequency (3) as well as disordered eating and body image dissatisfaction (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%